1995
DOI: 10.1021/bi00041a011
|View full text |Cite
|
Sign up to set email alerts
|

Multiple Binding with Identical Linkage: A Mechanism That Explains the Effect of Lipoprotein(a) on Fibrinolysis

Abstract: We have previously shown that both recombinant apo(a) and native Lp(a) inhibit the binding of Glu-plasminogen to fibrin surfaces [Fleury & Anglés-Cano (1991) Biochemistry 30, 7630-7638; Rouy et al. (1992) Biochemistry 31, 6332-6339]. The aim of the present study was to characterize the mechanism of this inhibition and to define the parameters governing binding when two different Lp(a) species compete with plasminogen for fibrin, a situation that may be found in vivo in subjects heterozygous for the apo(a) trai… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
51
0

Year Published

1997
1997
2021
2021

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 46 publications
(57 citation statements)
references
References 27 publications
5
51
0
Order By: Relevance
“…2). The dissociation constants calculated for plasminogen, K d = 1.16 F 0.22 Amol/l, and for apo(a), K d = 54 F 5 nmol/l, are in agreement with previously published data [12,27,29] in which fibrin was immobilised on multi-well plates using polymerised glutaraldehyde as a linker. This procedure has been previously proven to result in a fibrin monolayer that mimics a fibrin clot surface with regard to plasminogen binding and activation in a static system [27,40,41].…”
Section: Interactions Between Plasminogen and Mabs On A Fibrin Sensorsupporting
confidence: 90%
See 1 more Smart Citation
“…2). The dissociation constants calculated for plasminogen, K d = 1.16 F 0.22 Amol/l, and for apo(a), K d = 54 F 5 nmol/l, are in agreement with previously published data [12,27,29] in which fibrin was immobilised on multi-well plates using polymerised glutaraldehyde as a linker. This procedure has been previously proven to result in a fibrin monolayer that mimics a fibrin clot surface with regard to plasminogen binding and activation in a static system [27,40,41].…”
Section: Interactions Between Plasminogen and Mabs On A Fibrin Sensorsupporting
confidence: 90%
“…Among them, the lipoprotein Lp(a) [10], a highly atherogenic lipoprotein particle, which possesses multiple copies of plasminogen-like kringle 4 in its apolipoprotein(a), apo(a), moiety [11]. Lp(a) inhibits plasmin formation by competing with plasminogen for binding sites on fibrin and cell surfaces [12,13]. On the other hand, it has been demonstrated that the interaction of monoclonal antibodies with the low-or high-affinity LBSs of plasminogen may result in conformational changes yielding the plasminogen more susceptible to activation by plasminogen activators [14,15].…”
Section: Introductionmentioning
confidence: 99%
“…28,29,31 Furthermore, we have previously shown that in subjects heterozygous for the apo(a) trait, the influence of the various apo(a) isoforms on fibrinolysis depends on their affinity for fibrin and on their concentrations relative to each other and to plasminogen. 50 According to these data, high levels of Lp(a) and low plasminogen concentrations, conditions that were present in a majority of the nephrotic children included in the present study, may promote the deleterious effect of Lp(a). Indeed, congenital hypoplasminogenemia and high plasma levels of Lp(a) were recently associated with thrombosis.…”
Section: Discussionmentioning
confidence: 55%
“…50 In the present study, the binding assays were performed in plasma. Therefore, we sought to rule out potential confounding plasma factors that might influence the assay.…”
Section: Competitive Binding Of Plasma Lp(a) To Fibrin and Cell Surfacesmentioning
confidence: 99%
See 1 more Smart Citation